Caracterização morfológica de ocorrência de manganês por meio de dados geofísicos - Vieira, Leandro Ballarin [UNESP] (2015)
Some manganese supergenic occurences are found next to the Itapira city (SP, Brazil), representative of a trend that extends from Itapira/Socorro (SP) to Natércia/ Careaçu (MG), hosted by quartzites, schists and gneisses of the Itapira Group (Neoproterozoic). Several tectono-metamorphic events (from Paleoproterozoic to Neoproterozoic)affected the area regionally, resulting in a complex structural pattern represented by isoclinal folds, sometimes refolded and sheared. The ore/protore occurs as small bodies of manganese oxides and hydroxides, derived from the supergene alteration of gondite rocks. It is lenticular, rounded to elliptical in shape, with average dimensios of 100 m x 150 m, and dark gray to black in color. It is also locally associated with veins and lumps of quartz. Some of the occurences (Córrego do Cocho, Morro das Palmeiras e Soares) have been studied by others in terms of their mineralogy, petrography, geochemistry and ore processing aspects and X-Ray diffraction measurements showed significant amounts of graphite in the ore, up to 5%. This study aims the morphological characterization of the São Roque occurrence by integrating geological and geophysical investigations (DC-Resistivity and Induced Polarization. The geophysical data were obtained using a multi-electrode cable and the Electrical Resistivity Tomography (ERT) technique, using aWenner-Schlumberger array. Data were modelled through Res2dinv (2D geophysical inversion software for resistivity and IP data) software, where topographical data were included to generate 2D models in terms of resistivity and chargeability. The results showed that the manganese ore is related to low resistivity areas associated with high chargeability areas. Low resistivity results are correlated with highly saturated quartzites (host rocks) in depths below 30-35 meters, while high chargeability values are correlated ... (Complete abstract click electronic access below)